Literacy Across Disciplines: Integrating Reading and Writing in Content Areas to Foster Sustainable Development (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study investigates the impact of integrating literacy strategies across disciplines on students' academic performance in Wukari, Nigeria. Using a quasi-experimental design, the research involved 120 secondary school students divided into intervention and control groups. The intervention, implemented over 12 weeks, included math journals, close reading, reciprocal teaching, Socratic seminars, and digital storytelling. Data collection involved pre- and post-intervention assessments, surveys, and observations. Results showed significant improvements in students' scores across mathematics, social studies, and English Language (EL), with p-values less than 0.001. Qualitative data revealed enhanced student engagement and critical thinking. The findings align with Constructivist Learning Theory, supporting the role of active and social learning in knowledge construction. Key challenges included limited resources and teacher training, with solutions proposed in partnerships for resources and professional development. The study supports Sustainable Development Goal 4 (Quality Education) and offers practical recommendations for educators and policymakers to adopt literacy strategies for improved academic performance and educational equity.